EVALUATION OF THE NEURAC THERAPY EFFECTIVENESS FOR IMPROVING BALANCE AND WALKING IN PATIENTS WITH MULTIPLE SCLEROSIS (Physical Culture and Sport: Scientific Perspective, 2025)
Multiple sclerosis is a widespread chronic disease of the central nervous system that affects approximately 2.3 million people worldwide and is one of the most common causes of disability. The most typical disabling effects of multiple sclerosis on the motor sphere are impaired balance and gait, and increased fear of falling. Neuromuscular Activation Technique (Neurac) is a modern physical therapy method aimed at restoring and optimizing muscle activation through suspended exercises, which can help improve balance and gait in people with multiple sclerosis. The aim of the study was to evaluate the effectiveness of Neurac therapy, a method of neuromuscular activation, in improving balance and gait in patients with multiple sclerosis. Material and Methods: 57 patients with multiple sclerosis took part in the study, who were randomly divided into two groups: the intervention group (29 people) and the comparison group (28 people). The intervention group implemented a physical therapy program using Neurac therapy, while the comparison group used conventional balance exercises instead. The study design was comparative and non-blinded. The following research methods were used: analysis and synthesis of scientific and methodological literature, analysis of medical records, the Expanded Disability Status Scale in Multiple Sclerosis (EDSS), the «Up and Go» test, the Berg Balance Scale, the 10-meter walk test, and methods of mathematical statistics. Evaluation of the effectiveness of physical therapy programs demonstrated a statistically significant larger effect size for the intervention group in terms of balance and walking speed, and the Neurac physical therapy program contributed to more pronounced clinically significant changes for patients with multiple sclerosis.
Keywords: multiple sclerosis; physical therapy; gait; balance; rehabilitation; neuromuscular activation